Study of the Mechanical Properties of Bamboo and Glass Fiber Reinforced Hybrid Polymer Matrix Composites - Lawal, Ganiyu; Kuforiji, Catherine; Durowaye, Stephen; Kassim, Kehinde (Kathmandu University Journal of Science, Engineering and Technology, 2023)
Bamboo and glass fibers reinforced hybrid epoxy matrix composites were produced by stir casting method and the effects of production parameters (temperature, drying time, particle concentration, and bamboo-to-glass fiber ratio) on the mechanical properties were investigated. Overall optimum fabrication parameters are a bamboo fiber drying temperature of 25°C, a drying time of 20 mins, a particle size of 0.75 mm, and a bamboo-to-glass fiber ratio of 1:3. An in-depth analysis of the results shows that the improvement of different composite properties can be specifically targeted using different parameter combinations. Specifically, the shortest fibers below 0.75 mm, dried at room temperature for 60 minutes, and a bamboo-glass fiber ratio of 1:3 yielded the highest tensile strength of 7.47 MPa, which represents about 120 % increase as compared to unreinforced epoxy. Similarly, the longest fibers between 1 to 2.8 mm, dried at 110°C for 60 minutes, and a bamboo-glass fiber ratio of 1:1, exhibited the highest impact energy of 37.2 J, corresponding to about 79 % improvement. Moreover, the medium length fibers between 0.75 and 1 mm, dried at 80°C for 60 minutes, and a bamboo-glass fiber ratio of 3:1, exhibited the highest hardness of 16.73 HV, translating to 37% increase. Sample S8, which is the hybrid reinforced composite containing 0.75 mm bamboo fiber-particle size exhibited the lowest wear rate of 1.09 g/Nm implying the highest wear resistance. All these show the effectiveness of the mixture of bamboo and glass fibers in improving the mechanical properties of the composites. However, excessive bamboo concentration led to a significant reduction in wear properties.